PENGARUH PEMBERIAN DOSIS EM4 YANG BERBEDA DAN VITAMIN C ALAM PAKAN KOMERSIAL TERHADAP PERTUMBUHAN BERAT MUTLAK BENIH IKAN NILA MERAH (Oreochromis niloticus) - marom, khusnul; Madyowati, Sri Oetami; Agustini, Maria (Jurnal Perikanan Pantura (JPP), 2026)
Feed is an important input in aquaculture activities. Feed affects the growth and survival of fish which can increase the profits of aquaculture activities. This study aims to assess the effect of giving different doses of EM4 and vitamin C in commercial feed on the absolute weight growth of red tilapia (Oreochromis niloticus) aged 14 days. This study was conducted with four treatments A (Control), B (EM4 10 ml / kg feed and Vitamin C 150 gr / kg), C (EM4 15 ml / kg feed and Vitamin C 150 gr / kg feed) and D (EM4 20 ml / kg feed and Vitamin C 150 gr / kg feed). This study is expected to provide guidance to optimize the harvest of fishery cultivation activities. This study uses the analysis method of normality test in SPSS, homogeneity test of variance, analysis of variance and Least Significant Difference (LSD). The highest absolute weight growth of tilapia (Oreochromis niloticus) fry was obtained in treatment C with an EM4 dose of 15 ml/kg with an average yield of 2.4 g/fish. Supported by the results of water quality parameters including Temperature 28.2 0C -28.8 0C, pH 7.8-9 and Dissolved Oxygen (DO) 5.7-9 ppm. The addition of EM4 in treatment C is effective in increasing the growth of tilapia fry and has the potential to be recommended as an optimal dose in feed formulation to support growth performance.